A recent retrotransposon insertion of J caused E6 locus facilitating soybean adaptation into low latitude. Issue 6 (9th April 2021) - Fang, Chao; Liu, Jun; Zhang, Ting; Su, Tong; Li, Shichen; Cheng, Qun; Kong, Lingping; Li, Xiaoming; Bu, Tiantian; Li, Haiyang; Dong, Lidong; Lu, Sijia; et al.
Abstract: Soybean ( Glycine max ) is an important legume crop that was domesticated in temperate regions. Soybean varieties from these regions generally mature early and exhibit extremely low yield when grown under inductive short‐day (SD) conditions at low latitudes. The long‐juvenile (LJ) trait, which is characterized by delayed flowering and maturity, and improved yield under SD conditions, allowed the cultivation of soybean to expand to lower latitudes. Two major loci control the LJ trait: J and E6 . In the current study, positional cloning, sequence analysis, and transgenic complementation confirmed that E6 is a novel allele of J, the ortholog of Arabidopsis thaliana EARLY FLOWERING 3 ( ELF3 ). The mutant allele e6 PG, which carries a Ty1/Copia ‐like retrotransposon insertion, does not suppress the legume‐specific flowering repressor E1, allowing E1 to inhibit Flowering Locus T ( FT ) expression and thus delaying flowering and increasing yields under SD conditions. The e6 PG allele is a rare allele that has not been incorporated into modern breeding programs. The dysfunction of J might have greatly facilitated the adaptation of soybean to low latitudes. Our findings increase our understanding of the molecular mechanisms underlying the LJ trait and provide valuable resources for soybean breeding. Abstract : Our research confirmed that the soybean major long‐juvenile trait locus E6 is a novel allele of J . The mutant allele e6 PG, which carries a retrotransposon insertion, does not suppress the legume‐specific flowering repressor E1, allowing E1 to inhibit FT expression and thus delaying flowering and increasing yields under short‐day conditions.